The Long Week-End 1897-1919 : Part of a Life. - Bion, Wilfred (Karnac Books, 1982)
A reminiscence of the first twenty-one years of Wilfred Bion's life: eight years of childhood in India, ten years at public school in England, and three years of life in the army. 287 pages.